Exploring Glypican-3 targeted CAR-NK treatment and potential therapy resistance in hepatocellular carcinoma. - Lei Yang; Kien Pham; Yibo Xi; Qunfeng Wu; Dongfang Liu; Keith D Robertson; Chen Liu (PLoS ONE)
Hepatocellular carcinoma (HCC) is the most prevalent form of primary liver cancer and the second leading cause of cancer-related mortality globally. Despite advancements in current HCC treatment, it remains a malignancy with poor prognosis. Therefore, developing novel treatment options for patients with HCC is urgently needed. Chimeric antigen receptor (CAR)-modified natural killer (NK) cells have demonstrated potent anti-tumor effects, making them as a promising immunotherapy strategy for cancer treatment. Glypican-3 (GPC3), a cell surface oncofetal glycoprotein, is highly expressed in most HCC tissues, but not in normal tissues, and functions as a key driver of carcinogenesis. Given its high expression level on the cell surface, GPC3 is considered as an attractive immunotherapy target for HCC. In this study, two GPC3-specific CAR-NK cells, NK92MI/HN3 and NK92MI/HS20, were established using NK92MI cells, a modified IL-2-independent NK cell line. These cell lines were engineered with third generation GPC3-specific CARs, and their activities were subsequently evaluated in the treatment of HCC. We found that NK92MI/HN3 cells, rather than NK92MI/HS20 cells, exhibited a significant cytotoxicity effect against GPC3+ HepG2 cells in vitro and efficiently suppressed tumor growth in a xenograft model using NSG mice. In addition, irradiated NK92MI/HN3 cells displayed similar anti-tumor efficacy to unirradiated NK92MI/HN3 cells. Furthermore, we observed that NK92MI/HN3 cells showed higher killing activity against the GPC3 isoform 2 overexpression cell line (Sk-Hep1-v2) than those with GPC3 isoform 1 overexpression cell line (Sk-Hep1-v1). This suggest that the presence of different GPC3 isoforms in HCC may impact the cytotoxicity activity of NK92MI/HN3 cells and potentially influence therapeutic outcomes. These findings highlight the effective anti-HCC effects of NK92MI/HN3 cells and reveal the role of GPC3 isoforms in influencing therapy outcomes, suggesting that isoform analysis should be considered to optimize CAR-NK therapies to improve patient outcomes.